Truth and politics in the age of digital media - Barišić, Pavo (Array, 2019)
With the widespread omnipresence of digital social media, the truth has lost some of its reliability and objectivity, several authors warn nowadays. In fact, when an age brings to the foreground the tensions of truthfulness and falsehood, correct information and fake news, reality and fiction, genuineness and delusion, this testifies to the unpredictability and inscrutable nature of the confusion into which public communication has been entrained. The rapid development of new media and digital technologies is causing a far-reaching process of change, especially in the field of politics. In his book on “the post-truth era”, Ralph J. Keyes announced the advent of a “fib-friendly times”, in which “more lies than ever are being told” (Keyes 2004, 4). However, the considerations in this paper rest on a more cautious and critical approach. They support a viewpoint of pluriperspectivism. The new media have surely raised a challenge to contemporary communications. Political affairs are always about certain perspectives and contributions in the constant agon or contest of truth. There is no completely neutral and non-partisan claim to truth, as some philosophers and scientists aspired to represent. Because of its particular nature, the truth can be revealed only with controversy and effort, never without participation and beyond any perspectives. Nevertheless, neither does the truth decline nor do we enter an age of post-truth. Moreover, we can argue about the question which age tends more towards the lie and fake news. Politics is not in a more difficult state today than it has ever been, nor is it in a much simpler position in terms of truth. The truth remains for politics a supporting ground and a permanent benchmark for assessment. It can be discovered only in its pluri-perspective appearance.